Digital Diasporas: Labor and Affect in Gendered Indian Digital Publics - Sophie Del Fa (Communiquer)
This book review is an account of the most recent book by Gajjala Radhika, professor of Media and Communication (SMC) and of American Culture Studies (ACS) at Bowling Green State University, Ohio. Digital Diasporas: Labor and Affect in Gendered Indian Digital Publics explores the use of digital media by Indian women living abroad. The author gives a critical view of concepts such as, empowerment, digital streets and digital domesticity.affective labour, digital diaspora, indian diaspora, indian women, online feminism, Twitter